Transformation of The Agricultural Sector and Trade Openness to Indonesia's Economic Growth: Macroeconomic Analysis 1991–2023 - Hartini, Hartini; Ningsih, Liasulistia; Tanjung, Indra Ismayudi; Tanjung, Yulia Windi (Universitas Galuh, 2026)
Indonesia's economic structure, which is still dominated by the primary sector, particularly agriculture, presents its own challenges in promoting sustainable economic growth, especially amid the dynamics of global trade. This study aims to analyze the impact of the agricultural sector's contribution to Gross Domestic Product (GDP), the proportion of the workforce in the agricultural sector, and trade openness on Indonesia's economic growth. The method used is a quantitative approach with secondary data from the World Bank for the period 1991–2023. The analysis was conducted using multiple linear regression supported by classical assumption testing to ensure the validity of the estimation model. The results of the study indicate that the contribution of the agricultural sector and trade openness have a negative impact on economic growth, while the proportion of agricultural labor has a significant positive impact. These findings reflect the need to improve the quality and productivity of the agricultural labor force as a driver of growth, as well as the importance of formulating trade policies that support the strengthening of the domestic sector. This study makes an important contribution to the formulation of inclusive, sustainable economic development policies based on structural transformation of the agricultural sector.